Inter‐breeder differences in prepulse inhibition deficits of C57BL/6J mice in a maternal immune activation model - Yutaro Kobayashi; Hiroyoshi Inaba; Yuriko Iwakura; Hisaaki Namba; Hidekazu Sotoyama; Yui Murata; Kazuya Iwamoto; Hiroyuki Nawa (Wiley, 2021)
Abstract Genetic and environmental factors interact with each other to influence the risk of various psychiatric diseases; however, the intensity and nature of their interactions remain to be elucidated. We established a maternal infection model using polyinosinic‐polycytidylic acid (Poly(I:C)) to determine the relationship between the maternal breeding environment and behavioral changes in the offspring. We purchased pregnant C57BL/6J mice from three breeders and administered Poly(I:C) (2 mg/kg) intravenously in their tail vein on gestation day 15. The offspring were raised to 8‐12 weeks old and subjected to the acoustic startle tests to compare their startle response intensity, prepulse inhibition levels, and degree of the adaptation of the startle response. No statistical interaction between Poly(I:C) administration and sex was observed for prepulse inhibition; thus, male and female mice were analyzed together. There was a statistical interaction between the breeder origin of offspring and prepulse inhibition; the Poly(I:C) challenge significantly decreased prepulse inhibition levels of the offspring born to the pregnant dams from Breeder A but not those from the other breeders. However, we failed to detect significant inter‐breeder differences in Poly(I:C) effects on startle response and on startle adaptation with the given number of mice examined. The rearing environment of mouse dams has a prominent effect on the Poly(I:C)‐induced prepulse inhibition deficits in this maternal immune activation model.